Voice Based Email System for Blind People - Sai, C. Venkata; Thrinethra, D.; Devi, S.V.S. Ganga (Journal of Electronics and Informatics, 2023)
There are approximately 2.2 billion people who are blind or visually impaired in the world today. Emails are used to communicate critical and time-sensitive information. For a lot of visually impaired people, communication is difficult. Visually impaired people feel that they are more challenged than ever because technology is developing so quickly. The proposed system aims to develop an email system that would enable even untrained, visually impaired individuals to use communication services. This system involves the integration of voice recognition technology and natural language processing to enable the system to interpret and respond to user commands accurately. The user will only be able to utilize the mouse and speech-to-text conversion without using the keyboard. This system can also be useful for people who are not blind but have trouble reading. The system is user-friendly because it is dependent on interactive voice response.
Keywords: Speech-to-text converter; IVR (Interactive voice response); GUI (Graphical User Interfaces); SR(Speech recognition); GTTS (Google Text To Speech); and NLP(Natural Language processing)